Case Report: Primary Hyperparathyroidism due to Posterior Mediastinal Parathyroid Adenoma With One-Year Follow-Up - Shao, Yi; Zeng, Qingdong; Lv, Bin; Chen, Xu; Sheng, Lei (Frontiers in Surgery, 2022)
Ectopic parathyroid adenoma, though rare, is one of the causes of persistent hyperparathyroidism and recurrence of hyperparathyroidism. Ectopic parathyroid glands can be seen in thymus, thyroid, and mediastinum. However, ectopic parathyroid adenoma occurred in posterior superior mediastinum is extremely rare. Here, we report a case of primary hyperparathyroidism caused by ectopic parathyroid adenoma located in the posterior superior mediastinum. Serum parathyroid hormone, calcium, and vitamin D levels of the patient was followed up for one year.